In vivo characterization of the aortic wall stress-strain relationship - Asawinee Danpinid (2018)
Arterial stiffness has been shown to be a good indicator of arterial wall disease. However, a single parameter is insufficient to describe the complex stress-strain relationship of a multi-component, non-linear tissue such as the aorta. We therefore propose a new approach to measure the stress-strain relationship locally in vivo noninvasively, and present a clinically relevant parameter describing the mechanical interaction between aortic wall constituents. The slope change of the circumferential stress-strain curve was hypothesized to be related to the contribution of elastin and collagen, and was defined as the transition strain (θT). A two-parallel spring model was employed and three Young's moduli were accordingly evaluated, i.e., corresponding to the: elastic lamellae (E1), elastin-collagen fibers (E2) and collagen fibers (E3). Our study was performed on normal and Angiotensin II (AngII)-treated mouse abdominal aortas using the aortic pressure after catheterization and the local aortic wall diameters change from a cross-correlation technique on the radio frequency (RF) ultrasound signal at 30 MHz and frame rate of 8 kHz. Using our technique, the transition strain and three Young's moduli in both normal and pathological aortas were mapped in 2D. The slope change of the circumferential stress-strain curve was first observed in vivo under physiologic conditions. The transition strain was found at a lower strain level in the AngII-treated case, i.e., 0.029 ± 0.006 for the normal and 0.012 ± 0.004 for the AngII-treated aortas. E1, E2and E3were equal to 69.7 ± 18.6, 214.5 ± 65.8 and 144.8 ± 55.2 kPa for the normal aortas, and 222.1 ± 114.8, 775.0 ± 586.4 and 552.9 ± 519.1 kPa for the AngII-treated aortas, respectively. This is because of the alteration of structures and content of the wall constituents, the degradation of elastic lamella and collagen formation due to AngII treatment. While such values illustrate the alteration of structure and content of the wall constituents related to AngII treatment, limitations regarding physical assumptions (isotropic, linear elastic) should be kept in mind. The transition strain, however, was shown to be a pressure independent parameter that can be clinically relevant and noninvasively measured using ultrasound-based motion estimation techniques. In conclusion, our novel methodology can assess the stress-strain relationship of the aortic wall locally in vivo and quantify important parameters for the detection and characterization of vascular disease. © 2010 Elsevier B.V. All rights reserved.